Deglutição orofaríngea e ritmos biológicos na insuficiência renal crônica - Pinto, Aline Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Based on clinical observation of injury in the swallowing process in patients with chronic renal failure in hospital environment, in the present study the possibility of changes was investigated in oropharyngeal swallowing in this population. As the causes and possible consequences of dysphagia in chronic renal failure were not yet investigated, it also included the study of biological variables which demonstrably influence clinical parameters such as this one, and these are: sleep, melatonin production, a hormone produced by the pineal gland, with important function in circadian rhythm modulation of sleep-wakefulness and related to the immune system and inflammatory cytokine levels. The hypothesis of this study was that patients with chronic renal failure may have dysphagia conditions concomitant to sleep disorders, which are caused by deficits in melatonin production due to high levels of inflammatory cytokines. Objectives: To characterize the swallowing profile and sleep biological rhythmic variables, melatonin and inflammatory cytokines in patients with chronic renal failure. Methodology: The chronic renal failure group was composed of 20 people, the control group consisted of 19 healthy adult people. To swallowing assessment were used Videofluoroscopy and the Functional Oral Intake Scale (FOIS) and for sleep assessment - the Pittsburgh Sleep Quality Index questionnaire (PSQI - BR). For the melatonin dosage spit from people was collected at 4 hours break over 24 hours and to the cytokine dosage was performed the blood collect from 1 pm to 1 am. The measurements were performed using commercial kits through ELISA method. Results: Relating to swallowing in chronic renal failure, the Videofluoroscopy showed that 16 people had changes of oral and pharyngeal phase, three individuals had change only in pharyngeal phase and only one person presented unique changes of oral phase of swallowing. Previously to the Videofluoroscopy applying, it...

Baseado na observação clínica de prejuízo no processo de deglutição em indivíduos com insuficiência renal crônica (IRC) em âmbito hospitalar, no presente estudo foi investigada a hipótese de alterações na deglutição orofaríngea nesta população. Como as causas e possíveis consequências da disfagia na IRC ainda não foram investigadas o presente estudo contemplou também o estudo de variáveis biológicas que comprovadamente influenciam parâmetros clínicos como este, sendo estas o sono, a produção de melatonina, hormônio produzido pela glândula pineal, com papel importante na modulação do ritmo circadiano de sono-vigília e relacionado com sistema imune e os níveis de citocinas inflamatórias. A hipótese deste estudo seria de que pacientes com IRC podem apresentar quadros de disfagia concomitantemente a distúrbios de sono, sendo estes causados por déficit na produção de melatonina em consequência a altos níveis de citocinas inflamatórias. Objetivos: Caracterizar o perfil de deglutição e as váriaveis ritmicas biológicas sono, melatonina e citocinas inflamatórias em indivíduos com IRC. Metodologia: O grupo IRC foi composto por 20 indivíduos adultos, O grupo controle foi composto por 19 indivíduos adultos saudáveis, Para avaliação da deglutição foram utilizados a Videofluoroscopia (VFD) e a Functional Oral Intake Scale (FOIS) e para avaliação do sono o questionário do Índice de Qualidade de Sono de Pittsburgh (PSQI - BR). Para a dosagem de melatonina foi coletada saliva dos indivíduos em intervalos de 4 horas ao longo de 24 horas e para a dosagem de citocinas foi realizada coleta de sangue as 13:00h e a 1:00h. As quantificações foram realizadas utilizando-se kits comerciais pelo método ELISA. Resultados: Com relação a deglutição na IRC, a VFD mostrou que 16 indivíduos apresentaram alteração de fase oral e faríngea, três indivíduos alterações somente de fase faríngea...
Keywords: Insuficiencia renal; Disturbios da deglutição; Deglutição; Melatonina; Inflamação; Inflammation